Ecological Studies on Pteroma Pendula Joannis and Metisa Plana Walker (Lepidoptera: Psychidae) Towards Improved Integrated Management of Infestations in Oil Palm - Ho, Cheng Tuck (2002)
Pteroma pendula Joannis and Metisa plana Walker are important pests of the oil palm Elaeis guineensis Jacquin, which is the primary agricultural crop of Malaysia. Although there is a history of the integrated management of the bagworms, information gaps exist with regard to their incidence, biology, dispersion and population dynamics. Work of this thesis was aimed at overcoming these deficiencies and using the new information to improve integrated management of the pests. Analysis of historical records of bagworm infestations over 63,955 ha of oil palms in 69 estates in Peninsular Malaysia showed P. pendula and M plana to be the primary pests. Infestations were single species or mixed and ranged from nil to 7,8 11 ha per year. Cumulative infestation was 1 8,297 ha, 4,904 ha and 14,607 ha for single species P. pendula, M plana and mixed species P. pendula and M plana respectively. This showed P. pendula to be the predominant species. This was attributed to greater intrinsic rate of population increase, fm, and finite rate of population increase, A, for the species as well as its ability to survive very wet weather. Lower energy requirement for completion of life cycle and likewise propensity to balloon (which otherwise predisposed wash-off by rain) were established as reasons for this. Synchrony of P. pendula and M plana populations within and across estates was verified. Rainfall was indicated to be the primary factor synchronizing bagworm populations, particularly over wide areas, through their deleterious effects on survivorship of the pests. Short adult life span and overlapping if not synchronous emergence of males and females, pheromone-based male attraction to apterous females, regular dispersion of populations and natural enemies were postulated as other factors.